Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

De l’homosexualité à l’opéra - Champagne, Éric (L’Opéra : revue québécoise d’art lyrique, 2016)
Créée à l’Opéra de Montréal, l’œuvre de Kevin March, Les Feluettes, sur un livret de Michel Marc Bouchard, aborde de front une histoire d’amour entre deux hommes. Si les sujets homosexuels nous semblent communs dans la littérature, le théâtre et le cinéma, il faut se rendre à l’évidence qu’ils sont, du moins jusqu’à tout récemment, peu présents dans le monde de la musique, tous styles confondus. On entend beaucoup dire ces jours-ci que le genre de l’opéra, au public réputé conservateur, ne s’intéresse à cette thématique que depuis peu. Il s’agit en fait d’une demi-vérité, car s’il est vrai que l’homosexualité comme sujet principal n’est présent explicitement que dans des créations récentes, il se retrouve occasionnellement, caché ou crypté, dans diverses œuvres qui traversent son histoire vieille de plus de 400 ans.

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.